Los Objetivos del Buen Vivir. Una propuesta alternativa a los Objetivos de Desarrollo Sostenible - Antonio Luis HIDALGO-CAPITÁN; Santiago GARCÍA-ÁLVAREZ; Ana Patricia CUBILLO-GUEVARA; Ana Patricia CUBILLO-GUEVARA; Nancy MEDINA-CARRANCO (Revista Iberoamericana de Estudios de Desarrollo)
In the second section of this article we make a deconstruction of the Sustainable Development Goals (SDGs) through différance technique, to identify the main inconsistencies of the SDGs with respect to their purpose of contributing to the improvement of the well-being of humanity, from the perspective of trans-modern trans-development. We understand this concept as that way of life that allows human beings to coexist in harmony with other beings of nature, with other human beings and with ourselves. From this analysis, we concluded that the development implicit in the SDGs is really a model of unsustainable maldevelopment, based on coloniality-patriarchality-heteronormality of power-knowing-being, on capitalism and on anthropocentrism. And that has as consequences a global apartheid and an imperial way of life. Later, in the third section, we propose that, if the concept of good living emerged as an alternative to the concept of sustainable development, in the face of the international cooperation agenda of the SDGs, we can also make an alternative global agenda based on the Good Living Goals (GLGs). Thus, based on a normative research, from two discussion groups and a survey of experts, this section includes a proposal for GLGs, articulated in 3 general goals and 21 specific goals. All these goals would be aimed at achieving the three harmonies that should characterize global good living: biocentric sustainability, which would reflect harmony with all beings of nature; social equity, which would reflect harmony with all human beings; and personal satisfaction, which would reflect harmony with oneself.